2018
DOI: 10.1111/nep.13462
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and offspring risk of chronic kidney disease

Abstract: It is increasingly recognized that maternal obesity is implicated in developmental programming, contributing to the future risk of chronic disease development in offspring. The exact mechanisms of the role of maternal obesity in the development of chronic kidney disease in offspring remain unclear and animal models used are not without limitation. Human studies are limited by the effects of postnatal environmental conditions, which may have a direct impact on disease phenotype; and animal models are limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
8
1
1
Order By: Relevance
“…We confirmed several other risk factors for CKD in addition to preterm birth, including male sex, congenital anomalies, and maternal obesity, which are consistent with previous findings. 20 35 36 37 38 In contrast with a previous report, 30 we found that maternal pre-eclampsia also was associated with an increased risk of CKD in the offspring. Maternal pre-eclampsia has previously been associated with development of hypertension and cardiovascular disease in the offspring.…”
Section: Discussioncontrasting
confidence: 99%
“…We confirmed several other risk factors for CKD in addition to preterm birth, including male sex, congenital anomalies, and maternal obesity, which are consistent with previous findings. 20 35 36 37 38 In contrast with a previous report, 30 we found that maternal pre-eclampsia also was associated with an increased risk of CKD in the offspring. Maternal pre-eclampsia has previously been associated with development of hypertension and cardiovascular disease in the offspring.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, overnutrition in pregnancy is associated, in the short term, with an increase in the hypertensive disorders of pregnancy and, in the long term, almost paradoxically with the same diseases we find in an under-nourished population [6][7][8][9].…”
Section: Introductionsupporting
confidence: 49%
“…The consequences of obesity during pregnancy on the offspring renal function have been examined [28,38] but it was unknown to what extent the physiological renal hemodynamic changes are altered during gestation in overweighted subjects with an early and prolonged HFD. This study reports novel findings showing that RBF increases transitorily in rats with a HFD, but in the absence of a decrease in AP.…”
Section: Discussionmentioning
confidence: 99%